Analisis Framing Terhadap TKI Madura Dalam Pemberitaan Media Online Radar Madura - M. Zidan Arifaini; Imam Sofyan (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study examines how a local media outlet constructs the representation of migrant workers from Madura through its news coverage. The issue addressed in this research is the persistence of stereotyping and biased narratives surrounding migrant workers, which are often shaped by media framing. The objective of this study is to analyze how the identity of Madurese migrant workers is portrayed in news reports published by Radar Madura. This research employs a qualitative approach using framing analysis to interpret selected news articles from 2023 to 2025. The analysis focuses on how news structures, storytelling patterns, thematic emphasis, and language choices are used to construct meaning. The findings indicate that the media presents a dual representation, portraying migrant workers both as resilient contributors to the local economy and as vulnerable individuals facing exploitation and social challenges. These representations are influenced by cultural values, editorial perspectives, and local context. The study concludes that local media plays a significant role in shaping public perception and reinforcing both positive and negative images of Madurese migrant workers, which may affect broader social attitudes toward this group.